2021
DOI: 10.1002/glia.23997
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐mediated purinergic signaling is upregulated in a mouse model of Fragile X syndrome

Abstract: Fragile X syndrome (FXS) is the leading monogenic cause of intellectual disability and autism spectrum disorders. With increasing investigation into the molecular mechanisms underlying FXS, there is growing evidence that perturbations in glial signaling are widely associated with neurological pathology. Purinergic signaling, which utilizes nucleoside triphosphates as signaling molecules, provides one of the most ubiquitous signaling systems for glial‐neuronal and glial‐glial crosstalk. Here, we sought to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Unlike neurons, astrocytes are not electrically excitable cells, instead, they communicate via intracellular Ca 2+ elevation, which either occurs spontaneously or is evoked by environmental stimuli (Bazargani & Attwell, 2016). The increased peak amplitude of ATP‐induced Ca 2+ signaling we observed in FXS human astrocytes is consistent with a recent study of primary astrocytes from Fmr1 KO mice that identified upregulated ATP‐induced Ca 2+ signaling mediated by increased expression of purinergic receptors (Reynolds, Krasovska, & Scott, 2021; Reynolds, Wong, & Scott, 2021). Enhanced excitability has been well documented in the FXS field with hyper‐responsiveness and reduced adaptation to sensory stimulation and enhanced network synchronization (Castren et al, 2003; Contractor et al, 2015; Ethridge et al, 2016; He et al, 2017; Lovelace et al, 2016; Van der Molen et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike neurons, astrocytes are not electrically excitable cells, instead, they communicate via intracellular Ca 2+ elevation, which either occurs spontaneously or is evoked by environmental stimuli (Bazargani & Attwell, 2016). The increased peak amplitude of ATP‐induced Ca 2+ signaling we observed in FXS human astrocytes is consistent with a recent study of primary astrocytes from Fmr1 KO mice that identified upregulated ATP‐induced Ca 2+ signaling mediated by increased expression of purinergic receptors (Reynolds, Krasovska, & Scott, 2021; Reynolds, Wong, & Scott, 2021). Enhanced excitability has been well documented in the FXS field with hyper‐responsiveness and reduced adaptation to sensory stimulation and enhanced network synchronization (Castren et al, 2003; Contractor et al, 2015; Ethridge et al, 2016; He et al, 2017; Lovelace et al, 2016; Van der Molen et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, impairments in astrocyte function could exert a profound influence on the homeostasis of the brain, contributing to impairments in neurodevelopmental and neuropsychiatric disorders (de Majo et al, 2020; Molofsky et al, 2012; Pekny et al, 2016). Indeed, the absence of FMRP in astrocytes was found to contribute to the cellular and behavioral impairments in Fmr1 mutant animal models of FXS (Higashimori et al, 2013; Higashimori et al, 2016; Hodges et al, 2016; Jacobs et al, 2010; Reynolds, Krasovska, & Scott, 2021; Reynolds, Wong, & Scott, 2021). While these results based on the animal models suggest a critical contribution of astrocytes to the pathology of FXS, it remains unknown whether analogous astrocytic impairments are manifested in the FXS human brain.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, our previous studies have found that FMRP deficiency (especially from astroglia) downregulates functional expression of astroglial mGluR5 (Men et al, 2020) and GLT1 (Higashimori et al, 2013), both of which are highly enriched on the surface of astroglial processes. In addition, a recent study found increased expression of other surface functional proteins, such as purinergic P2Y 2 and P2Y 6 receptors, in astroglia of FMRP-deficient mice (Reynolds et al, 2021). Although the overall tdT 1 astroglial domain size is not affected by the lack of FMRP (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Cognitive decline with reduced cerebral blood flow has been described as an early marker of vascular dementia 83 and Alzheimer’s disease 84 , both of which were linked to astrocyte dysfunction 29 . Cerebrovascular impairments in neurodevelopmental conditions such as autism spectrum disorders 24 and schizophrenia 85 have also been associated with astrocyte malfunction 86 , 87 and reduced cerebral blood flow in adults 26 . As aberrant astrocyte morphogenesis and gliovascular development may predispose the adult brain to cognitive decline and/or impair vascular responses to neuronal injury, elucidating the role of HMGB1 in gliovascular plasticity may lead to therapies for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%